PARALLEL ALGORITHM TO FIND BAYES-NASH SOLUTION - Hancu, Boris; Gladei, Anatolie (Institutul de Matematică şi Informatică al Academiei de Ştiinţe a Moldovei, 2018)
We propose to use the new methodology for solving the com- plete and perfect information bimatrix game. To solve the ga- mes of these type we construct the incomplete and imperfect information game generated by the informational extended stra- tegies. Then we construct associated Bayesian game with non- informational extended strategies. For a HPC cluster computing system with shared and distributed memory, we constuct a paral- lel algorithm for computing Bayes-Nash solutions to the bimatrix informational extended games. The complexity and time perfor- mance analysis of the algorithm are provided.
Keywords: game; Bayes-Nash solution; parallel algorithm; Nash equilibrium; time complexity; communication complexity